The Effect of Using Quizizz toward Students' Grammatical Understanding - Ahlina, Hilyati; Forsia, Lastry (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2021)
This research aimed to know whether there was a significant effect of using Quizizz toward Students' Grammatical Understanding at the Eighth Grade of SMPN 108 Jakarta in Academic Year 2020/2021. The research was conducted from April 9, 2021 until April 30, 2021. This research used an experimental method, 36 students of 8-Class as a sample, which was determined by the English teacher herself and this research used a pre-experimental one-group pretest-posttest design. The writer collected the data using students' tests that there were pretest-posttest and observation sheet of Learning Process. The data were analyzed by mean, and Wilcoxon signed-rank test. The statistical results showed that there was a significant and has a positive effect of using Quizizz on the students' grammatical understanding at the Eighth Grade of SMPN 108 Jakarta in Academic Year 2020/2021 and the result of the observation sheet of learning process showed that the writer succeeded when did the learning process by using Quizizz in the class of 8-C's of SMPN 108 Jakarta in Academic Year 2020/2021. Therefore, it is recommended for teachers to use Quizizz as the alternative media in grammar teaching or English teaching and this research is expected to give information, model, or reference to be developed for further research.